The moderating effect of environmental dynamism on entrepreneurship and open innovation - Shichao Li; Kecheng Zhang (South African Journal of Economic and Management Sciences)
Background: The effect of entrepreneurship on open innovation under challenging environmental dynamics remains an unresolved issue critical for global economic progress, as the environmental dynamics alter businesses’ capacity for entrepreneurship.